Penerapan Supervisi Pendidikan untuk Meningkatkan Kompetensi Pedagogik Guru dalam Menyusun RPP Di UPTD Satdik SDN Tanggul Wetan 02 Kecamatan Tanggul Kabupaten Jember - Irfan, Nawawi (Jurnal Simki Postgraduate, 2023)
Professional teachers must have 5 (five) competencies, one of which is the competency in preparing lesson plans. However, in reality there are still many teachers who have not been able to prepare lesson plans so that this automatically affects the quality of the output produced in the learning process. Increasing the ability of teachers in preparing lesson plans can be done in various ways including through training, seminars, workshops, providing various guides and modules. However, after considering the various advantages and disadvantages, planned and continuous coaching through educational supervision is considered more effective because any problems found can be immediately sought for solutions together and the time can be adjusted according to the abilities of each teacher. This research was carried out using an action research design which was designed through two cycles through procedures: (1) planning (planning), (2) implementation of action (action), (3) observation (observation), (4) reflection (reflection) in each cycle. The results showed that, in formulating indicators of effective learning objectives in accordance with competency standards and basic competencies of each subject, there was an increase of 10 points, in choosing strategies and methods, there was an increase of 9 points, in determining assessment techniques and methods that could measure the achievement of objectives. experienced an increase of 7 points, in determining learning materials / learning materials experienced an increase of 8 points, in preparing learning evaluations an increase of 11 points. In this way, it can be said that educational supervision of class teachers can improve the ability of teachers at the UPTD Satdik SDN Tanggul Wetan 02 in preparing lesson plans.